Special Issue: Advances in Opportunistic Viral Infections II - Carlo Contini; Roberto De Giorgio; Matteo Guarino; Martina Maritati (Viruses)
Since the 1980s, particular opportunistic viral infections (OVIs) have been associated with HIV/AIDS infection, a pandemic still not eradicated as late diagnoses continue to emerge each year, leading to a high mortality and lethality rate [...]